Transparent lithium aluminum silicate glass ceramic

Optimized transparent lithium aluminum silicate glass ceramics address the challenge of high lithium costs by maintaining thermal stability and reducing color distortion, achieving high heat resistance and optical clarity for cooktops and peeping windows.

JP2025015489APending Publication Date: 2025-01-30SCHOTT AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024114554
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing transparent lithium aluminum silicate glass ceramics face challenges in reducing lithium content due to soaring raw material prices while maintaining thermal stability, heat resistance, and minimizing color distortion, especially when used as cooktops or peeping windows.

Method used

The composition of the glass ceramics is optimized with specific ranges of SiO2 (62-70%), Al2O3 (19-23%), Li2O (2.4-3.4%), and additional components to achieve a thermal expansion coefficient of -0.8 to 1.5 ppm/K, saturation C* less than 6, and Akiko diameter less than 80 nm, ensuring high heat resistance and low light scattering.

Benefits of technology

The solution provides transparent glass ceramics suitable for cooktops and peeping windows with improved thermal stability, heat resistance, and reduced color distortion, maintaining high transmittance and optical clarity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015489000001
    Figure 2025015489000001
  • Figure 2025015489000002
    Figure 2025015489000002
  • Figure 2025015489000003
    Figure 2025015489000003
Patent Text Reader

Abstract

To provide a transparent lithium aluminum silicate glass ceramic suitable for use as a cooktop for cooking devices.SOLUTION: A glass ceramic has a coefficient of thermal expansion of -0.8 to 1.5 ppm / K in the range of 20°C and 700°C, a chroma value C* of less than 6 at a thickness of 4 mm, and a crystallite size of less than 80 nm in a high-quartz solid solution phase. The glass ceramic comprises, expressed in weight percent on an oxide basis, SiO2: 62-70, Al2O3: 19-23, Li2O: 2.4-3.4, Na2O: 0-1, ZnO: 0-5, TiO: 21.5-2.5, ZrO2: 1.5-2.5 and SnO2: 0-0.15. The glass ceramic does not contain Cr2O3, V2O5, MnO2 or MoO3, other than unavoidable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to transparent lithium aluminum silicate glass-ceramics, particularly suitable for use as cooktops in cooking appliances, and to their uses.

[0002] Background of the Invention Glass-ceramics, particularly transparent glass-ceramics, have been known for a long time. One variant of such glass-ceramics also known in the prior art is lithium aluminum silicate (LAS) glass-ceramics, which contain either a high-quartz solid solution (HQMK) for particularly transparent materials or a keatite solid solution (KMK) for particularly translucent or opaque materials as the predominant crystalline phase. To produce such glass-ceramics, a starting glass, known as a green glass, is first prepared by methods conventional in glassmaking. This green glass is then converted into a glass-ceramic by a heat treatment known as ceramization. The transparent glass-ceramics thus produced can be used in a wide variety of applications. In particular, such glass-ceramics are used as cooktops. Furthermore, such glass-ceramics are used as stovetop and oven viewing windows, worktops, or safety glass.

[0003] An essential property of these materials used as cooktops is their very low coefficient of thermal expansion in the temperature range from room temperature to 700°C. This low coefficient of thermal expansion results in high thermal shock resistance. The coefficient of thermal expansion is set by the combination of a crystalline phase with a negative coefficient of thermal expansion and a residual amorphous glass phase with a positive coefficient of thermal expansion. For this reason, conventional glass-ceramics typically contain lithium oxide in proportions of more than 3.6% by weight up to 5.0% by weight.

[0004] Due to the rising cost of lithium as a raw material, it is advantageous for economic reasons to minimize the proportion of lithium in glass-ceramics. However, lithium is one of the three main components of lithium aluminum silicate glass-ceramics, and therefore cannot be simply reduced at will. The proportion of Li2O directly affects key properties of glass-ceramics, such as their viscosity during melting and hot forming, which is important for manufacturability, and their coefficient of thermal expansion, which is important for use as cooktops.

[0005] The trend in lithium prices is nothing new. The price of lithium has been steadily increasing for the past 20 years. Despite this long-standing need, most commercially available glass-ceramics for cooktops contain more than approximately 3.8% LiO by weight.

[0006] Glass-ceramics with a proportion of LiO of less than 3.5% by weight are known from WO 2012 / 010341, EP 3502069, US 2017050880, US 2020189965, US 2020140322, US 2021387899, and WO 2021 / 224412. However, these glass-ceramics have various drawbacks, such as reduced thermal shock resistance and poor melting properties of the green glass.

[0007] A basic approach that allows the production of lithium aluminum silicate glass-ceramics that avoid the above-mentioned disadvantages even with a low LiO content has been described by the applicant, for example, in German Utility Model No. 202022106826, where an approach that allows the production of transparent glass-ceramics with a low LiO content is also described.

[0008] In addition to the temperature stability mentioned above, transparent glass-ceramics have other special requirements. When transparent glass-ceramics are used as cooktops, they are usually provided with a colored underside coating so that heating elements and associated electronics located below the glass-ceramic are not visible from above. In this case, it is generally required that the color perception of such underside coating by the end user is not distorted by the glass-ceramic. When transparent glass-ceramics are used as viewing windows, similar requirements are imposed on the glass-ceramic because, in this case too, color distortion when viewed through the viewing window must be avoided.

[0009] Transparent glass-ceramics are understood herein, as is customary, to mean glass-ceramics with low light scattering, the transmittance of which can be adjusted over a wide range using absorbing, i.e. coloring, components.

[0010] Problems to be Solved by the Invention The object of the present invention is to provide a transparent lithium aluminum silicate glass ceramic that is cost-effective, but does not impose limitations on its application properties. Furthermore, it is desirable that the glass ceramic according to the present invention distorts color perception as little as possible.

[0011] Glass-ceramics are particularly desirable for use as cooktops with all types of heating elements, including radiant, induction, and gas heating elements, which require a sufficiently high thermal shock resistance as well as a high long-term heat resistance.

[0012] Summary of the Invention The problem of the present invention is solved by the subject matter of the independent claims. Preferred embodiments and developments can be found in the dependent claims.

[0013] The transparent lithium aluminum silicate glass ceramic of the present invention has a thermal expansion coefficient of -0.8 to 1.5 ppm / K in the range of 20°C to 700°C, and a chroma C * less than 6, preferably less than 5.5, and the crystallite size in the high quartz solid solution phase is less than 80 nm, wherein the glass-ceramic comprises the following components in the indicated amounts, in weight percent on an oxide basis: SiO262~70 Al2O319~23 Li2O 2.4~3.4 Na2O 0~1 ZnO 0-5 TiO2 1.5-2.5 ZrO21.5~2.5 SnO20~0.15.

[0014] Here, the glass ceramic further does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0015] Glass-ceramics with an appropriate thermal expansion coefficient combine high thermal shock resistance with high long-term thermal stability, making them suitable for use as cooktops with any type of heating element. The thermal expansion coefficient is at least -0.8 ppm / K, where "ppm" stands for "parts per million," i.e., 10 parts per million for a temperature change of 1 K. -6 This refers to the relative magnitude change in the coefficient of thermal expansion. Shifting the coefficient of thermal expansion towards more negative values ​​is to be avoided. A negative coefficient of thermal expansion, i.e., contraction, generates tensile stresses on the surface of the glass-ceramic during heating. At values ​​below -0.8 ppm / K, these stresses can reduce the mechanical strength of the cooktop at typical operating temperatures of the cooking appliance. A coefficient of thermal expansion above 1.5 ppm / K is also to be avoided. A coefficient of thermal expansion above 1.5 ppm / K does not ensure sufficient thermal shock resistance for the use of glass-ceramics in cooking appliances with radiant heating elements.

[0016] In one development of the invention, the thermal expansion coefficient is at least −0.6 ppm / K, −0.4 ppm / K, −0.2 ppm / K, 0.0 ppm / K, 0.2 ppm / K, 0.4 ppm / K, 0.6 ppm / K, or even 0.8 ppm / K. Furthermore, the thermal expansion coefficient is advantageously at most 1.4 ppm / K, 1.3 ppm / K, 1.2 ppm / K, 1.1 ppm / K, 1.0 ppm / K, 0.8 ppm / K, or even at most only 0.6 ppm / K.

[0017] In a preferred embodiment of the invention, the glass-ceramics have a thermal expansion coefficient of -0.8 to 0.8 ppm / K, advantageously -0.5 to 0.5 ppm / K, particularly preferably -0.3 to 0.3 ppm / K. Such glass-ceramics are particularly suitable for cooktops of cooking appliances equipped with radiant or induction heating elements.

[0018] With regard to the optical properties given in terms of transmittance and saturation of the glass-ceramics according to the invention, "at a thickness of 4 mm" means that the corresponding properties are measured on a sample with a material thickness of 4 mm or are measured at another material thickness and converted to a material thickness of 4 mm.

[0019] Saturation C * L * a * b * It is determined from the color coordinates according to the following formula:

number

[0020] Color coordinates a * and b * is determined in a known manner from the transmission spectrum of the glass ceramic using standard illuminant D65 and a 2° observer.

[0021] Saturation C *A value of less than 6, preferably less than 5.5, ensures that the color of light passing through the glass-ceramic is only slightly altered, which is particularly important when used as a viewing window for a cooktop or fireplace, for example.

[0022] The saturation of glass-ceramics is particularly noticeable when they are coated with a white or generally light-colored underside coating, for example, when used as a cooktop. Glass-ceramics for such applications are often 4 mm thick. This means that the light reflected by the backside coating has to travel an 8 mm optical path, and color shifts due to the inherent color of the glass-ceramic have a greater effect than in the case of shorter optical paths. Therefore, a correspondingly low saturation is particularly advantageous for cooktops or fireplace viewing windows with a white coating on the backside. Preferably, the glass-ceramics according to the invention have a saturation C of less than 5.5, in particular less than 5. * It has.

[0023] Here, the glass ceramics according to the present invention have a crystallite size of less than 80 nm, preferably less than 70 nm, particularly preferably less than 60 nm, and very particularly preferably less than 50 nm in the high-quartz solid solution phase. In this case, the crystallite size has a direct effect on the optical properties of the glass ceramics. For example, if the crystallite size is too large, the light scattering in the glass ceramics increases, which appears as cloudiness of the glass ceramics.

[0024] The glass ceramic according to the invention comprises the following components in % by weight: SiO262~70, Al2O319~23, and Li2O 2.4~3.4.

[0025] The elements SiO2 and Al2O3 form the main crystalline phase together with Li2O in glass-ceramics. At the same time, they largely determine the glass-forming properties and viscosity of the green glass.

[0026] The SiO2 content of the glass-ceramics according to the present invention should be a maximum of 70% by weight, since this component significantly increases the viscosity of the glass, particularly the processing point. Higher SiO2 contents are uneconomical for achieving good glass melting and low forming temperatures. If the SiO2 proportion is too high, exceeding 70% by weight, keatite may form during ceramization. This leads to a significant increase in the thermal expansion coefficient and a deterioration of the optical properties of the material, particularly in the form of haze. The minimum SiO2 content here should be 62% by weight, since this is advantageous for the desired properties, such as chemical and heat resistance.

[0027] Advantageously, the glass-ceramic contains at least 63 wt. %, or even 64 wt. % SiO2. The more SiO2 contained in the glass-ceramic, the better its heat and chemical resistance. Furthermore, the glass-ceramic advantageously contains no more than 69 wt. %, no more than 68 wt. %, no more than 67 wt. %, no more than 66 wt. %, or even no more than 65 wt. % SiO2. The less SiO2 contained in the glass-ceramic, the better the meltability and processability of the green glass in hot forming.

[0028] The Al2O3 content of the glass-ceramics according to the present invention is in the range of 19-23 wt. Higher Al2O3 proportions lead to problems of devitrification and undesired mullite formation. Therefore, it should not exceed 23 wt. An Al2O3 content below 19 wt. % is detrimental to the formation of a high-quartz solid solution and promotes the formation of undesirable crystalline phases. It has also been found that a low Al2O3 content adversely affects the saturation of the glass-ceramics.

[0029] Advantageously, the glass-ceramic contains at least 20% by weight of Al2O3. The more Al2O3 contained in the glass-ceramic, the better its heat resistance. Furthermore, the glass-ceramic advantageously contains up to 22% by weight of Al2O3, advantageously up to 21.5% by weight of Al2O3. The less Al2O3 contained in the glass-ceramic, the better the meltability and processability of the green glass in hot forming.

[0030] The Li2O content of the glass ceramics according to the present invention is in the range of 2.4 to 3.4 wt. It has been found that a Li2O content in this range, combined with the remaining components within the stated limits, allows for the production of glass ceramics with high thermal shock resistance and good melting properties. Because Li2O significantly affects the thermal expansion coefficient of the glass ceramics, the Li2O content is selected within the stated limits in combination with the remaining components of the glass ceramics according to the present invention to achieve the thermal shock resistance required for the present invention. Additionally, a Li2O content greater than 2.4 wt. % reduces the electrical resistance and viscosity of the glass melt, thereby lowering the processing point and thus favorably affecting the manufacturability of the glass ceramics. The reduced viscosity of the glass melt also improves the efficiency of the fining process. This improved fining process reduces production waste due to bubble formation in the green glass. Li2O also reduces the tendency of the green glass to devitrify.

[0031] In a preferred embodiment, the glass-ceramic comprises at least 2.5 wt. %, 2.6 wt. %, or even 2.7 wt. % Li2O.

[0032] The lithium sources used for glass-ceramics production are usually natural mineral sources such as spodumene and petalite, or synthetically produced Li2CO3.

[0033] In a preferred embodiment, the glass-ceramic comprises a high-quartz solid solution as the predominant crystalline phase. "Predominant crystalline phase" means that the glass-ceramic comprises a higher volume fraction of high-quartz solid solution than keatite solid solution and other crystalline phases. In one development of this embodiment, the glass-ceramic comprises <10 vol.%, preferably <5 vol.%, particularly preferably <3 vol.% of keatite solid solution. Here, these volume % data are relative to the volume of the glass-ceramic. The volume fraction is determined by Rietveld refinement from X-ray diffraction spectra.

[0034] Keatite solid solutions generally have a higher thermal expansion coefficient than high-quartz solid solutions. Therefore, in order to reduce the thermal expansion coefficient of a glass-ceramic, it is particularly preferable to increase the proportion of high-quartz solid solutions while simultaneously decreasing the proportion of keatite solid solutions. A low thermal expansion coefficient also improves the thermal shock resistance of the glass-ceramic. At the same time, keatite solid solutions typically have a large crystallite size, which causes strong light scattering, so an excessively high proportion of keatite can adversely affect the optical properties of the glass-ceramic. For this reason, the content of keatite in the crystalline phase should be kept as low as possible.

[0035] In addition to the aforementioned amounts of SiO2, Al2O3, and Li2O, the glass-ceramics according to the present invention contain 0 to 1 wt. % Na2O. Here, a 0 to 1 wt. % Na2O content in the glass-ceramics according to the present invention further improves meltability and devitrification behavior during glass forming. Furthermore, Na2O can increase the electrical conductivity of the melt, facilitating energy coupling from an electric heater in the melting tank. However, there is a limit to its content, since it is not incorporated into the crystalline phase but remains essentially in the residual glass phase of the glass-ceramics. An excessively high content impairs the crystallization behavior during the conversion of a crystallizable starting glass to a glass-ceramic, particularly at the expense of a high ceramization rate. Consequently, the higher the ceramization rate of the glass-ceramics, the larger the crystallite size, which unfavorably affects the scattering behavior of the glass-ceramics. Furthermore, a high content unfavorably affects the long-term durability / heat resistance of the glass-ceramics. For this reason, the glass-ceramics advantageously contain >0.1-1 wt. %, or 0.2-0.8 wt. %, or even 0.3-0.6 wt. % Na2O.

[0036] The glass-ceramics according to the present invention further contain 0 to 5 wt. % ZnO, preferably 1.2 to 4.0 wt. % ZnO, more preferably 1.4 to 3.6 wt. % ZnO, and particularly preferably 1.4 to 3.0 wt. It has already been explained above that Li2O contributes to a reduction in the thermal expansion coefficient of the glass-ceramics. Therefore, if the Li2O content is reduced below the level typically used in transparent glass-ceramics in the prior art, the reduction in the thermal expansion coefficient of the high-quartz solid solution in the glass-ceramics may be reduced, making it impossible to achieve the expansion coefficient required for use as a cooktop. However, because ZnO, like Li2O, also contributes to a reduction in the thermal expansion coefficient, the effect of reducing the Li2O content can be at least partially offset by adjusting the ZnO content.

[0037] ZnO also lowers the processing point and upper devitrification temperature of glass-ceramics. However, excessive ZnO content increases the refractive index difference between the crystalline phase and the residual glass phase in the glass-ceramic, causing the corresponding glass-ceramic to scatter incident light more strongly. As a result, excessive ZnO content can adversely affect the transmittance and color saturation of the glass-ceramic.

[0038] In addition to the above-mentioned components, the glass-ceramics according to the present invention also contain 1.5 to 2.5 wt. % TiO2. TiO2, together with ZrO2, significantly contributes to nucleation. Here, the amount of TiO2 is limited to a value of 2.5 wt. % or less, preferably 2.4 wt. % or less. Higher amounts of TiO2 can cause devitrification during hot forming. This can lead to an undesirable increase in the refractive index of the residual glass phase. At the same time, the glass-ceramics contain at least 1.5 wt. %, preferably at least 1.6 wt. %, at least 1.7 wt. %, at least 1.8 wt. %, at least 1.9 wt. %, at least 2.0 wt. %, or even at least 2.1 wt. A high TiO2 content accelerates nucleation, thereby shortening the ceramization time of the glass-ceramics. A low content stabilizes the ceramization process and prevents unintended devitrification during hot forming of the green glass. In summary, the upper limit of the TiO2 content is set in order to keep the coloring effect of TiO2 on the optical properties of the glass-ceramics as low as possible, but at the same time, it is undesirable to choose the TiO2 content too low, so as to still ensure sufficient nucleation and short ceramization times.

[0039] Furthermore, the glass ceramic according to the present invention contains 1.5 to 2.5 wt. % ZrO2. ZrO2 acts particularly as a nucleating agent in the glass ceramic and can interact with other components of the glass ceramic, such as SnO2 and TiO2. To improve nucleation, a ZrO2 content of more than 1.5 wt. % is advantageous. At the same time, it is advantageous to limit the ZrO2 content to 2.5 wt. % because ZrO2 deteriorates the melting behavior of the batch. Furthermore, ZrO2 can cause devitrification during hot forming. This can lead to the formation of undesirable Zr-containing crystalline phases, such as baddeleyite. Preferably, the glass ceramic contains at least >1.6 wt. %, particularly preferably >1.7 wt. %, and very particularly preferably >1.8 wt. % ZrO2. Furthermore, the glass ceramics advantageously contain 2.4 wt.%, 2.3 wt.%, 2.2 wt.%, 2.1 wt.%, 2.0 wt.%, or even only 1.9 wt.% or less ZrO2. At these amounts, a particularly good compromise can be achieved between a positive contribution to nucleation and still acceptable deterioration in meltability and hot forming. Here, optimizing the ZrO2 content, particularly taking into account the TiO2 content in the glass ceramic, can further enable faster ceramization of the green glass. Faster ceramization upon sufficient preceding nucleation leads to smaller crystallite sizes and less light scattering in the glass ceramic. Furthermore, the use of ZrO2 allows the proportion of TiO2 as an additional nucleating agent to be reduced, thereby producing glass ceramics with reduced saturation.

[0040] The glass-ceramics of the present invention further contain 0 to 0.15 wt. % SnO2. SnO2 assists in the fining process of green glass. Therefore, glass-ceramics containing the above-mentioned amounts of SnO2 are characterized by a particularly low level of defects due to trapped gas bubbles. SnO2 is furthermore advantageous in ensuring sufficient nucleation for the properties of the present invention when combined with the other components of the glass-ceramics of the present invention.

[0041] However, SnO2 should not exceed 0.15% by weight, as this can adversely affect the optical properties of glass-ceramics, particularly increasing their color saturation. This is especially true because SnO2, together with TiO2, can form additional absorption bands for incident light, resulting in a red shift of the transmitted light. Furthermore, high SnO2 contents can lead to the undesirable crystallization of Sn-containing crystalline phases, such as cassiterite, on contact materials (e.g., Pt / Rh) during molding, further deteriorating the optical properties of the glass-ceramics. Therefore, limiting the SnO2 content as much as possible is particularly beneficial for the optical properties of glass-ceramics.

[0042] Thus, according to a further embodiment, it is provided that the transparent lithium aluminum silicate glass-ceramic contains not more than 0.13 wt. % SnO, preferably not more than 0.12 wt. % SnO, preferably not more than 0.11 wt. % SnO. In this way, the adverse effect of SnO on the optical properties of the glass-ceramic can be further reduced, while the SnO content ensures sufficient fining of the green glass.

[0043] The glass ceramics according to the present invention further do not contain Cr2O3, V2O5, MnO2, or MoO3, except for unavoidable impurities. V2O5 and MoO3 are usually used as the primary colorants for coloring volume-colored glass ceramics, while Cr2O3 and MnO2 are often used as secondary colorants. Since the aforementioned colorants, especially V2O5, generally color glass ceramics very intensely even in small amounts, it is desirable to minimize the content of the aforementioned components in the glass ceramics according to the present invention in order to ensure the color saturation of the glass ceramics according to the present invention. These components are present, inter alia, as impurities in the raw materials of the batch or as components in cullet added to the batch to improve melting properties. "Avoidable impurities" here is understood to mean a content of the respective components in the composition of less than 20 ppm, particularly less than 10 ppm, and in particular less than 5 ppm. Furthermore, the glass ceramics preferably do not contain Ce, Ni, Cu, Co, W, and / or S, or their oxides, except for unavoidable impurities.

[0044] In one development of the invention, the transparent lithium aluminum silicate glass ceramic has a light transmittance τ of more than 80% at a thickness of 4 mm. vis It is further provided that the present invention has the following structure:

[0045] Glass ceramics with a light transmission of more than 80% at a thickness of 4 mm are particularly suitable for use as fireplace viewing windows or cooktops. In fireplaces, this transmission allows particularly good visibility of the fire. In cooking appliances, this transmission allows particularly good visibility of relatively low-brightness optical displays, such as LCD displays or OLED displays. Preferably, the glass ceramics according to the invention here have a light transmission τ of more than 82%, particularly preferably more than 85%, at a thickness of 4 mm. vis It has.

[0046] The above transmittance data for glass-ceramics are also for a thickness of 4 mm, and can be converted to other substrate thicknesses using the Beer-Lambert law. Here, the light transmittance τ vis is measured in the wavelength range of 380-780 nm using standard illuminant D65 and a 2° observer according to the specifications of DIN 5033. This value corresponds to the luminance Y in the CIExyY color space.

[0047] In order to support the fining of the green glass, it has now been found that, in addition to the SnO content mentioned above, a proportion of up to 1.5 wt. % of As2O3 and / or Sb2O3 is advantageous in order to reduce the SnO2 content as much as possible, since, as already explained above, SnO2, in addition to its positive effect on the fining of the green glass, can have a negative effect on the optical properties of the glass-ceramic. The expression "As2O3 and / or Sb2O3" here and below means that these two components may be present in the glass-ceramic either alone or together, whereby both components can account for up to 1.5 wt. % independently of one another.

[0048] Thus, according to a further development of the present invention, the glass-ceramic is provided as being free of SnO2, except for unavoidable impurities, and containing 0.5 to 1.5% by weight of As2O3 and / or Sb2O3. A fining process that is completely free of SnO2, thus avoiding the aforementioned influence of SnO2 on the optical properties of the glass-ceramic, is particularly advantageous for producing transparent, color-neutral glass-ceramics. Unlike SnO2, As2O3 and Sb2O3 do not affect the color of the glass-ceramic, especially since their use in combination with TiO2 does not lead to increased coloring.

[0049] In summary, therefore, glass-ceramics can be refined by the addition of SnO2 alone, by the combination of SnO2 with As2O3 and / or Sb2O3, or by fining with As2O3 and / or Sb2O3, i.e., in the absence of SnO2.

[0050] In one development of the invention, the glass ceramics contain less than 0.05% by weight, preferably less than 0.04% by weight, particularly preferably less than 0.03% by weight, and very particularly preferably less than 0.02% by weight of Fe2O3. Similar to V2O5, Cr2O3, MnO2, and MoO3, Fe2O3 also has a coloring effect in glass ceramics. For this reason, limiting the Fe2O3 content to the values ​​mentioned above is advantageous for transparent glass ceramics. For example, glass ceramics containing Fe2O3 as a colorant often have a yellowish tint. This can occur, for example, in glass ceramics that simultaneously contain TiO2 and Fe2O3 introduced as a result of raw material impurities. This effect occurs particularly in glass ceramics that have been refined with SnO2, because SnO2 dissolves the Fe in Fe2O3. 2+ This is because the addition of TiO2 to the glass-ceramics increases the proportion of , which in turn can contribute to increased coloring. If such glass-ceramics are provided with a white undercoating, the undercoating will have a clearly perceptible yellowish tint.

[0051] Furthermore, Fe2O3 affects transmittance not only in the visible light range but also in the near-infrared range up to wavelengths of approximately 3 μm. Therefore, Fe2O3 not only influences the realization of certain colors and the displayability of color displays, but also the absorption in the near-infrared range determines how much heat energy the glass melt can absorb in the vessel, which in turn determines how much heat power from the radiant heating element can pass through the glass-ceramic. This also determines whether and what infrared sensors can be used in stovetops. Such sensors can be designed, for example, as optical touch sensors or infrared receivers for wireless data transmission.

[0052] It should be noted that within the scope of this disclosure, the components of the glasses are presented in the form that is usually obtained by analysis, where each component is usually presented in its stable, usually highest oxidation state, although it is pointed out that this does not necessarily correspond to the form in which the component actually exists.

[0053] For example, iron in oxide glasses is present in both divalent and trivalent forms, i.e., Fe 2+ or as FeO, or Fe 3+ or Fe2O3. Thus, the data on the content of the corresponding components within the scope of this disclosure relate to the usual data of the analysis, but it is understood that each component may also be present in a form that deviates from the "ideal" oxidation state that is usually indicated.

[0054] In one further development of the invention, it is further provided that the transparent lithium aluminum silicate glass-ceramic contains 0.01 to 0.07 wt. % Nd2O3, preferably 0.03 to 0.06 wt. % Nd2O3. In this case, Nd2O3 contributes to offsetting the saturation of the glass-ceramic due to SnO2, especially when fining is performed with SnO2. In this case, the addition of Nd2O3 is advantageous for producing an almost color-neutral glass-ceramic, especially when the SnO2 content is greater than 0.1 wt. %.

[0055] In glass-ceramics with Fe2O3 and TiO2 contents within the above limits, the addition of Nd2O3 can also reduce or eliminate the yellow tint caused by Fe2O3 and TiO2, while only slightly affecting light transmittance. This effect is due to the narrow absorption bands of Nd2O3 in the visible light range at wavelengths of 513, 526, 575, 585, and 745 nm, which is particularly advantageous for producing transparent, color-neutral glass-ceramics.

[0056] In one development of the invention, the glass ceramic further contains less than 1 wt. K2O in an amount of 0 to <1 wt. can improve the meltability and devitrification behavior during glass forming. K2O can also increase the electrical conductivity of the melt, facilitating the coupling of energy from an electric heater in the melting bath. However, there is a limit to the content, since it is not incorporated into the crystalline phase but remains essentially in the residual glass phase of the glass ceramic. An excessively high content impairs the crystallization behavior during the conversion of the crystallizable starting glass to the glass ceramic, particularly at the expense of a high ceramization rate. Similar to the above explanation for Na2O, in this case too, an excessively high ceramization rate and therefore a large crystallite size in the glass ceramic adversely affect the scattering behavior of the glass ceramic. Furthermore, a high content adversely affects the long-term durability / heat resistance of the glass ceramic.

[0057] These properties are further improved if KO is included in the glass-ceramics in an amount of 0.8 wt%, 0.6 wt%, 0.5 wt%, 0.4 wt%, or even 0.3 wt% or less. In one particular embodiment, it can be further provided that the glass-ceramics are free of KO, except as unavoidable impurities.

[0058] In one development of the invention, the glass ceramic contains less than 0.6 wt. %, preferably less than 0.5 wt. %, particularly preferably less than 0.4 wt. % MgO, which has a positive effect on the meltability and devitrification behavior of the glass ceramic, and limiting the MgO content to the above-mentioned limits can contribute to optimizing the thermal expansion coefficient of the glass ceramic and reducing the color saturation.

[0059] According to a further development of the invention, it is further provided that the transparent lithium aluminum silicate glass ceramic contains less than 1 wt. %, preferably less than 0.6 wt. %, and particularly preferably less than 0.5 wt. % CaO. In this case, CaO has a beneficial effect on the devitrification behavior of the glass ceramic. However, since CaO contributes to an increase in the crystallite size in the glass ceramic, it has been found to be advantageous for colorless, transparent glass ceramics to limit the CaO content to the above-mentioned values. An increase in the crystallite size is accompanied by increased scattering, thus degrading the optical properties of the glass ceramic.

[0060] It has already been mentioned above that the stated ZnO contents in the glass ceramics according to the invention can contribute to increased scattering, since an excessively high ZnO content contributes to an increase in the refractive index difference between the crystalline phase and the residual glass phase in the glass ceramic. To counteract this effect, glass ceramics according to further embodiments preferably further contain more than 1.8 wt. % BaO, preferably more than 2.5 wt. % BaO, particularly preferably more than 2.8 wt. % BaO. As the BaO content increases, the tendency of the glass ceramic to scatter incident light decreases, since the addition of BaO allows the refractive index of the residual glass phase with the same crystallite size to be equal to the refractive index of the crystalline phase of the glass ceramic. This effect is observed when the proportions of LiO and ZnO are within the above-mentioned limits, especially when the glass ceramic simultaneously contains low amounts of SrO and CaO.

[0061] BaO, like LiO, also reduces the viscosity of the glass melt and thus the processing point. To improve the meltability of the green glass, it is advantageous for the glass ceramic to contain more than 2.6 wt. %, more than 2.7 wt. %, more than 2.8 wt. %, more than 2.9 wt. %, or even more than 3.0 wt. % BaO in combination with the above-mentioned amount of LiO. In the glass ceramic, BaO also significantly contributes to improving the devitrification behavior of the green glass during hot forming.

[0062] However, it has been found that BaO adversely affects the formation of crystalline phases during ceramization, and therefore, to prevent the need for long ceramization times, the amount of BaO is preferably limited to a maximum of 5.0 wt%, 4.5 wt%, 4.0 wt%, 3.9 wt%, 3.8 wt%, 3.7 wt%, 3.6 wt%, or even 3.5 wt%.

[0063] In a further development of the invention, the ratio of Al2O3 to TiO2 is in the range of 7 to 12, preferably in the range of 8 to 11, particularly preferably in the range of 8.5 to 10.5. It has been found that a ratio of Al2O3 to TiO2 in this range has a particularly advantageous effect on the saturation of the glass-ceramics while at the same time allowing a particularly stable ceramization.

[0064] In one development of the invention, the glass ceramic comprises the following components in % by weight, based on oxides: SiO263~70 Al2O319~23 Li2O 2.4~3.4 Na2O 0.1~1 K2O 0~0.8 MgO 0~0.6 CaO 0-1 BaO >1.8 ZnO 1-4 TiO2 1.5-2.5 ZrO21.5~2.5 SnO20~0.15.

[0065] Here, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0066] Furthermore, such glass-ceramics may contain SrO, the SrO content of which is primarily due to impurities in the raw materials used to produce the glass-ceramics. In this case, SrO contributes, among other things, to the scattering of light by the glass-ceramics. Therefore, it is advantageous to keep the SrO content in the glass-ceramics as low as possible.

[0067] The following table contains three further developments of the composition in % by weight on an oxide basis of the glass-ceramics according to the invention: [Table 1]

[0068] Here, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0069] Furthermore, such glass-ceramics may in particular be free of K2O and As2O3 and Sb2O3, except for unavoidable impurities.

[0070] In contrast to this, three alternative developments of the composition of the glass ceramic according to the invention comprise the following components in % by weight on an oxide basis: [Table 2]

[0071] Here, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0072] Furthermore, such glass-ceramics may in particular be free of K2O and As2O3 and Sb2O3, except for unavoidable impurities.

[0073] Three further developments of the composition of the glass ceramic according to the invention comprise the following components, expressed in % by weight, on an oxide basis: [Table 3]

[0074] Here, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0075] In this development, the fining of the green glass based on the composition mentioned above can be carried out using SnO2, or a combination of SnO2 with As2O3 and / or Sb2O3, or only As2O3 and / or Sb2O3, i.e., in the absence of SnO2, where the above-mentioned limit values ​​can be set for the content of the respective components in the composition.

[0076] Three further developments of the composition of the glass ceramic according to the invention comprise the following components, expressed in % by weight, on an oxide basis: [Table 4]

[0077] Here, such glass-ceramics may in particular be free of As2O3 and Sb2O3, except for unavoidable impurities.

[0078] Three further developments of the composition of the glass ceramic according to the invention comprise the following components, expressed in % by weight, on an oxide basis: [Table 5]

[0079] Here, the glass ceramic does not contain Cr2O3, V2O5, MnO2 and MoO3 except for unavoidable impurities.

[0080] Furthermore, such glass-ceramics may in particular be free of As2O3 and Sb2O3, except for unavoidable impurities.

[0081] The glass ceramics according to the invention are used as cooktops, fireplace sight glasses, grill or roasting tops, covers for combustion elements of gas grills, oven sight glasses, in particular oven sight glasses for pyrolysis furnaces, kitchen or laboratory workbenches or table tops, covers for lighting devices, in fire glazing and as safety glass, optionally in laminated composites, as carrier plates or as linings for furnaces in thermal processes or as back covers for portable electronic devices.

[0082] The glass ceramics according to the invention can be used in particular as cooktops. In this case, the cooktops can be provided with a decorative or functional coating on all or part of the top and / or bottom surface. Touch sensors for operating the cooktop can also be provided on the bottom surface. These can be, for example, printed, glued or pressure-bonded capacitive sensors.

[0083] The present invention will now be further illustrated by the following examples.

[0084] The crystallizable green glasses of the examples were melted for 4 hours at temperatures between 1620°C and 1680°C from industrial batch raw materials commonly used in the glass industry. This selection of raw materials allows for both economical raw materials and low levels of undesirable impurities. After melting the batch in a sintered silica glass crucible, the melt was poured into a Pt / Rh crucible with a silica glass inner crucible and homogenized by stirring at temperatures between 1600°C and 1640°C for 60 minutes. After homogenization, the glasses were refined at temperatures between 1640°C and 1680°C for 3 to 3.5 hours. The glasses were then poured into a mold measuring approximately 120 x 120 x 30 mm. 3 Blocks of this size were produced and cooled to room temperature in a cooling furnace at 30 K / h, starting from 650-680 °C depending on the viscosity of the glass, to relieve stress. The cast pieces were divided into those required for testing and those required for ceramization.

[0085] Ceramization of the samples in the green glass state was carried out in a ceramization process having the following steps: a) heating from room temperature to 740°C within 25 minutes; b) holding the temperature at 740°C for 20 minutes; c) increasing the temperature from 740°C to 780°C within 6.5 minutes; d) increasing the temperature from 780°C to 825°C within 20 minutes; e) increasing the temperature from 825°C to 910°C within 8.5 minutes; f) holding the temperature at 910°C for 10 minutes; g) Cooling to room temperature within 125 minutes.

[0086] This ceramization process should be considered exemplary: by varying the temperatures and times of the individual steps or by adding further steps, such as additional holding times, it is possible to fine-tune the properties of the glass-ceramics.

[0087] Ceramization can be carried out, for example, with the following parameters: a) Heat from room temperature to 680℃-760℃ within 3-60 minutes; b) The crystallizable green glass is formed at a nucleation temperature range T a Heat up to 800°C in 10 to 100 minutes. c) The glass containing the crystallization nuclei is heated to a temperature range of 810°C to 930°C, which is a temperature range with a high crystal growth rate, within 5 to 80 minutes. d) maintaining a temperature of 810 to 930°C for 2 to 60 minutes; e) Cool to room temperature within less than 150 minutes.

[0088] The following table contains the compositions and material properties of examples according to the present invention.

[0089] Here, the coefficient of thermal expansion CTE was measured by a method substantially based on the 1998 edition of DIN ISO 7991.

[0090] To measure the upper limit of devitrification temperature (OEG), green glass was melted in a Pt / Rh10 crucible. The crucible was then held at various temperatures within the processing temperature range for 5 hours. The highest temperature at which the first crystals appear at the interface between the glass melt and the crucible wall determines the OEG.

[0091] The working point (T4) of the green glass was measured using a stirring viscometer in accordance with DIN ISO 7884-2.

[0092] When green glass transforms into glass-ceramics, the density increases because the crystalline phase is denser than the amorphous glass. The so-called shrinkage ratio describes the linear change in length when green glass transforms into glass-ceramics. The shrinkage ratio in percent is calculated from the density of the green glass and the density of the glass-ceramic as follows:

number

[0093] T g denotes the transformation temperature of the green glass, also known as the glass transition temperature, which is measured by dilatometry.

[0094] Light transmittance τ vis is measured in the wavelength range of 380-780 nm using standard illuminant D65 and a 2° observer according to the specifications of DIN 5033. This value corresponds to luminance Y in the CIExyY color space. This value is a measure of luminance perception by the human eye.

[0095] The transmission spectra were measured in accordance with ISO 15368:2021. Table 2 lists examples of the spectral transmittance "T@···" at wavelengths of 470 nm, 600 nm, 630 nm, 700 nm, 950 nm, and 1600 nm.

[0096] The color coordinates in the CIExyY and CIELab color spaces were determined according to the specifications of CIE 1932 using a 2° observer and transmitted light of standard illuminant D65.

[0097] All transmittance measurements were performed on 4 mm thick samples that were smooth on both sides.

[0098] The "HQMK phase content" which is the volume fraction and the "HQMK crystallite size" which is the crystallite size of the crystalline phase were determined from the X-ray diffraction spectrum by Rietveld analysis.

[0099] [Table 6-1] [Table 6-2] [Table 6-3] [Table 6-4]

[0100] [Table 7-1] [Table 7-2] [Table 7-3] [Table 7-4]

Claims

1. A transparent lithium aluminum silicate glass ceramic, comprising: A thermal expansion coefficient in the range of 20°C to 700°C is -0.8 to 1.5 ppm / K; Saturation C at a thickness of 4 mm * is less than 6, The crystallite size in the high quartz solid solution phase is less than 80 nm; The following, in weight percent on an oxide basis: Yes 2 62~70 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 11~23 Li 2 O 2.4~3.4 Na 2 O 0~1 ZnO 0-5 TO 2 1.5~2.5 ZrO 2 1.5~2.5 SnO 2 0~0.15 having a composition comprising The glass ceramics contains Cr, excluding unavoidable impurities. 2 O 3 , V 2 O 5 , MnO 2 and MoO 3 A transparent, non-toxic, lithium aluminum silicate glass-ceramic.

2. The transparent lithium aluminum silicate glass ceramic has a light transmittance τ of more than 80% at a thickness of 4 mm. vis 2. The transparent lithium aluminum silicate glass-ceramic of claim 1, characterized in that it has

3. The transparent lithium aluminum silicate glass ceramics have a SnO content of 0.13% by weight or less, preferably 0.12% by weight or less, and particularly preferably 0.11% by weight or less. 2 3. The transparent lithium aluminum silicate glass ceramic according to claim 1, comprising:

4. The transparent lithium aluminum silicate glass ceramic contains SnO except for unavoidable impurities. 2 and 0.5% to 1.5% by weight of As 2 O 3 and / or Sb 2 O 3 4. The transparent lithium aluminum silicate glass ceramic according to claim 1, further comprising:

5. The transparent lithium aluminum silicate glass ceramics preferably contain less than 0.05% by weight, more preferably less than 0.04% by weight, particularly preferably less than 0.03% by weight, very particularly preferably less than 0.02% by weight of Fe. 2 O 3 5. The transparent lithium aluminum silicate glass ceramic according to claim 1, comprising:

6. The transparent lithium aluminum silicate glass ceramic contains 0.01 to 0.07 wt. % Nd 2 O 3 6. The transparent lithium aluminum silicate glass ceramic according to claim 1, comprising:

7. The transparent lithium aluminum silicate glass ceramics preferably have a K content of less than 1% by weight, preferably less than 0.7% by weight, particularly preferably less than 0.5% by weight, very particularly preferably less than 0.3% by weight. 2 7. The transparent lithium aluminum silicate glass ceramic according to claim 1, further comprising O.

8. 8. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that it contains less than 0.6% by weight, preferably less than 0.5% by weight, particularly preferably less than 0.4% by weight, of MgO.

9. 9. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that it contains less than 1% by weight, preferably less than 0.6% by weight, particularly preferably less than 0.5% by weight of CaO.

10. 10. The transparent lithium aluminum silicate glass ceramic according to claim 1, characterized in that it contains more than 1.8% by weight, preferably more than 2.5% by weight, particularly preferably more than 2.8% by weight of BaO.

11. TiO 2 Al 2 O 3 11. The transparent lithium aluminum silicate glass ceramic according to claim 1, wherein the ratio is in the range from 7 to 12, preferably in the range from 8 to 11, particularly preferably in the range from 8.5 to 10.

5.

12. The glass-ceramic comprises, in weight percent on an oxide basis: Yes 2 63~70 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 11~23 Li 2 O 2.4~3.4 Na 2 O0.1~1 K 2 O 0~0.8 MgO 0-0.6 CaO 0-1 BaO>1.8 ZnO 1-4 TO 2 1.5~2.5 ZrO 2 1.5~2.5 SnO 2 0~0.15 The glass ceramic contains Cr, except for unavoidable impurities. 2 O 3 , V 2 O 5 , MnO 2 and MoO 3 12. The transparent lithium aluminum silicate glass ceramic according to claim 1, wherein the glass ceramic is free of

13. 13. Use of the glass ceramics according to any one of claims 1 to 12 as cooktops, fireplace sight glasses, grill or roasting tops, covers for combustion elements of gas grills, oven sight glasses, in particular oven sight glasses of pyrolysis furnaces, kitchen or laboratory workbenches or table tops, covers for lighting devices, in fire protection glazing and as safety glass, optionally in laminated composites, as carrier plates or as linings for furnaces in thermal processes or as back covers for portable electronic devices.